Islamophobia, fear of loss of freedom, and the Muslim woman - Carland, Susan (Islam and Christian-Muslim relations, 2011)
This article looks at the way Islamophobia and the fear of loss of freedom intersect and the divergent ramifications of this. Recent international examples involving Muslim women are used for illustration. The article argues that fear of loss of freedom can lead to Islamophobia against Muslim women in the West, and that Islamophobia can lead to a loss of freedom for Muslim women in the West, in a constant loop. In particular, the article discusses the burqa ban in France and the development of the Eurabia myth. This European manifestation of Islamophobia has hardened attitudes towards Muslims, which has resulted in the loss of physical freedom for Muslim women in the West. This reverse loss of freedom is examined through the case of Marwa el-Sherbini.